2023
DOI: 10.1111/fwb.14091
|View full text |Cite
|
Sign up to set email alerts
|

Closing the life‐history loop: Density effects on fecundity and egg size of an exploited, amphidromous fish (Galaxias maculatus) in freshwater protected areas

Abstract: 1. Understanding how fecundity and egg size respond to density-dependent and density-independent processes is essential for fisheries assessments because it shows managers how exploited populations respond to fishery closures. Similarly, the extent to which density-dependent and density-independent processes influence fecundity and egg size in freshwater protected areas (FPAs) is important for determining their conservation potential and effectiveness as a fisheries enhancement strategy.2. The fecundity and eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The datasets and underlying code supporting this article are available on figshare: . The data are provided in electronic supplementary material [57].…”
Section: Data Accessibilitymentioning
confidence: 99%
“…The datasets and underlying code supporting this article are available on figshare: . The data are provided in electronic supplementary material [57].…”
Section: Data Accessibilitymentioning
confidence: 99%
“…On the contrary, Boy et al [15] reported no correlation between fecundity, weight, and length for this species. Fecundity can also be affected by several factors, including environmental sources, nutrition, genetic differences, or a combination of them [50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%